Development and Validation of a Self-Assessment Instrument for Measuring TPACK Ability of Scientific-Based Chemistry Teachers - Hairida, Hairida; Erlina, Erlina; Rasmawan, Rahmat; Sartika, Rody Putra; Ifriany, Andi; Arifiyanti, Fitria; Natasya, Qois; Warohmah, Mawaddatul (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2023)
This research aims to establish the validity and reliability of a novel self-assessment instrument designed to quantify the Technological Pedagogical Content Knowledge (TPACK) abilities of chemistry teachers implementing a science-based approach. The study employs a Research and Development (R&D) framework, utilizing the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The development process involved two subject matter experts for initial validity testing, followed by a panel of 18 expert reviewers for further validity assessment, and a reliability testing phase involving 50 active chemistry teachers. Initial validity assessment yielded Aiken's V coefficient values of 0.92 and 0.96 for the two experts, demonstrating high agreement on the instrument's content validity. Further validation by the expert panel resulted in an average Aiken's V coefficient of 0.94, indicating excellent consensus on the instrument's relevance and applicability. Reliability testing exhibited a satisfactory level of consistency, with Aiken's V coefficient values ranging from 0.52 to 0.64 for the seven TPACK domains (PK, CK, TK, TCK, TPK, PCK, TPACK). Consequently, the developed self-assessment instrument exhibits both robust validity and reliability in evaluating TPACK abilities of science-based chemistry teachers. The findings recommend the instrument's utility in facilitating better understanding of TPACK abilities in this context, contributing to the body of research on pedagogical tool development and supporting professional development efforts among scientific-based chemistry educators.